2020
DOI: 10.1101/2020.11.19.390609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peroxisome import stress impairs ribosome biogenesis and induces integrative stress response through eIF2α phosphorylation

Abstract: Peroxisome biogenesis diseases (PBDs) are characterized by global defects in peroxisomal function and can result in severe brain, liver, kidney, and bone malfunctions. PBDs are due to mutations in peroxisome biogenesis factors (PEX genes) that are responsible for peroxisome assembly and function. There is increasing evidence suggesting that peroxisome import functions decline during aging. The transcriptome profiling of peroxisome import defects is still lacking. To identify conserved responses, we undertook a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 120 publications
(138 reference statements)
2
8
0
Order By: Relevance
“…Accordingly, the silencing of PEX2 in human liver hepatocarcinoma cell lines induced the mRNA expression of ER stress markers such as PERK, Erol-Lα, PDI, and CHOP [ 122 ]. Our recent study also supports the link between peroxisomal dysfunction and ER stress [ 9 ]. We found that the ER-associated protein degradation (ERAD) pathway was induced in Pex1 , Pex5 , and Pex12 knockdowns in Drosophila.…”
Section: Cellular Responses To Peroxisomal Dysfunctionsupporting
confidence: 87%
See 4 more Smart Citations
“…Accordingly, the silencing of PEX2 in human liver hepatocarcinoma cell lines induced the mRNA expression of ER stress markers such as PERK, Erol-Lα, PDI, and CHOP [ 122 ]. Our recent study also supports the link between peroxisomal dysfunction and ER stress [ 9 ]. We found that the ER-associated protein degradation (ERAD) pathway was induced in Pex1 , Pex5 , and Pex12 knockdowns in Drosophila.…”
Section: Cellular Responses To Peroxisomal Dysfunctionsupporting
confidence: 87%
“…Several lines of evidence suggest that an uncharacterized cellular stress response pathway might exist in eukaryotic cells to cope with peroxisomal dysfunction. Recent studies have revealed global transcriptional changes in PEX mutants with impaired peroxisomal import [ 9 , 68 , 69 , 70 , 71 , 72 ]. Peeters et al [ 68 ] investigated the role of peroxisomes in liver carbohydrate metabolism through a microarray analysis using hepatocyte-specific Pex5 knockout mice ( L-Pex5 −/− mice).…”
Section: Cellular Responses To Peroxisomal Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations